Escrita da língua de sinais em comunidades do Orkut: marcador cultural na educação de surdos - Zappe, Carla Tatiana (2010)
This work is situated in the field of Cultural Studies in Education, and articulated with theoretical issues from Deaf Studies. It aims at investigating the movement towards Sign Writing in Deaf Education through discussion forums in Orkut communities. Such interest caused me to know and research about Sign Writing, leading me to observe discourses produced in Orkut communities as discursive practices in which words have power and produce meanings. I have considered the following issues: Is it necessary to translate Sign Language into its written form? Can Sign Writing be understood as a deaf cultural translation? How can we think of Sign Writing as a deaf cultural mark as well as a deaf identity formation? From these guiding questions, a methodological path has been delineated in order to approach the theme, and the research has focused on discursive productions about Sign Writing. Three communities dealing with Sign Writing have been found in Orkut. I myself have designed a community called Escrita da Língua de Sinais along the research, aiming at fostering discussions. Questions have been formulated so as to observe the movement of members belonging to each community. A few manifestations have been noticed as a response to the first questioning, but less than expected. I supposed that a larger number of comments would be richer. Such situation led me to perceive that the discursive materiality of forums is interesting to be analyzed, regardless its quantity. As the low participation in the communities was unexpected, I have focused my study on the community that presented the largest number of forums and, consequently, of active members. In the narratives found, discussions about teaching and learning Sign Writing have been highlighted, which I have categorized together with the idea of in-between . In the interstices of this study, I have found some of my research questions. The meaning of writing Sign Language has been understood as a deaf cultural mark that goes beyond noticeable issues related to teaching and learning. I have found evidences of cultural markers in which discourses produce discussions about learning and its importance, going beyond methodological issues the importance of belonging to deaf culture, thus strengthening the difference of being deaf.